Restitution as a Prerequisite for Case Termination: Analyzing Conditional Exoneration in Russian Criminal Procedure - Grinenko, Aleksandr; Ivanov, Dmitriy; Kleshchina, Elena; Alyshkin, Vladislav; Bezryadin, Viktor (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2024)
In this scholarly article, the researchers methodically examine the protocols involved in discontinuing criminal cases through the conciliation of the involved parties, as well as ceasing criminal prosecution on the grounds of active contrition, contingent upon the pivotal requirement of recompensing the damage inflicted by the criminal act. The study substantiates that the investigator, or the individual responsible for the preliminary inquiry, bears the mandatory duty to ascertain, via investigative measures, that the injury wrought by the criminal offence has been comprehensively redressed. The authors delineate that the transcript of the victim's interrogation is the most prevalent procedural document, signifying that the conciliation procedures are mutually satisfactory, voluntary, and indicative of the parties' willingness and preparedness to reconcile. Conclusively, the authors infer that exemption from criminal accountability and the consequent cessation of the criminal case, predicated upon reconciliation or earnest remorse, is contingent upon the substantiated evidence of actual compensation for the harm engendered by the criminally punishable deed.